AadA36, a novel chromosomal aminoglycoside nucleotidyltransferase from a clinical isolate of Providencia stuartii - Gao, Mengdi; Feng, Chunlin; Ji, Yongan; Shi, Yaokai; Shi, Weina; Zhang, Lei; Liu, Shuang; Li, Anqi; Zhang, Xueya; Li, Qiaoling; Lu, Junwan; Bao, Qiyu; et al. (Frontiers in Microbiology, 2022)
In this study, we characterized a novel chromosome-encoded aminoglycoside nucleotidyltransferase (ANT), AadA36, from the Providencia stuartii strain P14 isolated from the sputum specimen of a burn patient at a hospital in Wenzhou, China. Among the functionally characterized ANTs, AadA36 shared the highest amino acid sequence identity of 51.91% with AadA14. The whole genome of P. stuartii P14 consisted of one chromosome and two plasmids (designated pP14-166 and pP14-114). A total of 19 genes with ≥80% similarity with functionally characterized antimicrobial resistance genes (ARGs) were identified in the whole genome, including aminoglycosidess (aac(2’)-Ia, aph(6)-Id, aph(3'')-Ib, aac(6')-Ib, ant(3'')-IIa, aph(3')-Ia), β-lactams (blaCMY-2 and blaOXA-10) and so on. Antimicrobial susceptibility testing showed that the aadA36 gene conferred specific resistance to spectinomycin and streptomycin, and the minimum inhibitory concentration (MIC) of these antimicrobials increased 128- and 64-fold compared with the control strain. The kinetic parameters of AadA36 were consistent with the MIC data of spectinomycin and streptomycin, with kcat/Km ratios of (1.07±2.23)×104 M-1s-1 and (8.96±1.01)×103 M-1s-1, respectively. Comparative genomic analysis of multidrug resistance regions harbored by the plasmid pP14-166 demonstrated the transmissibility of these resistance genes among different bacterial species. The identification of a novel aminoglycoside resistance gene will help us further understand the complexity of the resistance mechanisms and provide deep insights into the dissemination of resistance genes in the microbial population.